Insular life in the global village: current paradoxes (Polis (Santiago), 2018)
The author starts playing with nineteenth century quotations that seem to describe the context of globalization, to then present the concepts of global village, change of era, and triple insularisation of human history, as an 'umbrella' of cultural globalization. Then develops the paradoxical faces of globalization, namely: the counterpoint between interdependence and vulnerability in economy, between presence and anonymity in communication, and between a universal access to image and concentration of money; to finally bring these distinctions to a proposal for Latin America, living among the disillusionment with national projects and the expectation of social integration. In this context, argues that the collective production of meaning is a black box.
Keywords: globalization; insularisation; national projects; social integration